Experiment and Simulation Effects of Cyclic Pitch Control on Performance of Horizontal Axis Wind Turbine - Sang, Le Quang; Maeda, Takao; Kamada, Yasunari; Li, Qing'an (Center of Biomass & Renewable Energy, Diponegoro University, 2017)
Offshore wind is generally stronger and more consistent than wind on land. A large part of the offshore wind resource is however located in deep water, where floating wind turbines can harvest more energy. This paper describes a systematic experiment and a simulation analysis (FAST code) about the cyclic pitch control of blades. This work was performed to investigate performance fluctuation of a floating wind turbine utilizing cyclic pitch control. The experiment was carried out in an open wind tunnel with mainstream wind velocity of 10 m/s with the front inflow wind and the oblique inflow wind conditions. A model wind turbine is two-bladed downwind wind turbine with diameter of 1.6 m. Moment and force acts on the model wind turbine were measured by a six-component balance. Fluctuation of power coefficient and thrust coefficient was investigated in the cyclic pitch control. The model wind turbine and the experimental conditions were simulated by FAST code. The comparison of the experimental data and the simulation results of FAST code show that the power coefficient and thrust coefficient are in good agreement.Â Keywords: Floating Offshore Wind Turbine, Aerodynamic Forces, Cyclic Pitch Control, FAST Code, Wind Tunnel ExperimentArticle History: Received February 11stÂ 2017; Received in revised form April 29th 2017; Accepted June 2nd 2017; Available onlineHow to Cite This Article: Sang, L.Q., Maeda, T., Kamada, Y. and Li, Q. (2017) Experiment and simulation effect of cyclic pitch control on performance of horizontal axis wind turbine to International Journal of Renewable Energy Development, 6(2), 119-125.https://doi.org/10.14710/ijred.6.2.119-125